2004
DOI: 10.1007/s00066-004-1268-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calculation Algorithm on Dose Distribution in Irradiation of Non-Small Cell Lung Cancer (NSCLC)

Abstract: . The CC and PB calculation algorithms result in different dose distributions in case of lung tumors. Particularly the minimum dose to the PTV, which may be relevant for tumor control, is significantly lower for CC. Since it is generally accepted that the CC algorithm describes secondary particle transport more exactly than PB models, the use of the latter should be critically evaluated in the treatment planning of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Our 3D-CRT results are similar to these reported by Koelbl et al [24]: V 95 of the PTV is overestimated by PB, and PB underestimates low doses and overestimates high doses in the lung, when compared to CC.…”
Section: Imrtsupporting
confidence: 81%
See 2 more Smart Citations
“…Our 3D-CRT results are similar to these reported by Koelbl et al [24]: V 95 of the PTV is overestimated by PB, and PB underestimates low doses and overestimates high doses in the lung, when compared to CC.…”
Section: Imrtsupporting
confidence: 81%
“…Intensitymodulated radiotherapy (IMRT), imageguided radiotherapy (IGRT), and stereotactic body radiotherapy (SBRT) facilitate optimization of dose to target, lung, breasts and heart in radiotherapy for mediastinal Hodgkin lymphoma, lung cancer or breast cancer [6,7,8,9,10]. Expanding on previous reports on dose calculation accuracy of various algorithms [11,12,13,14,15,16,17,18,19,20,21,22], dose calculation with advanced algorithms had been evaluated for different lung tumor geometries for 3D-conformal radiotherapy (3D-CRT) [23,24,25]. Concern had, however, been raised regarding the effects of dose calculation uncertainties of algorithms implemented in commercial IMRT treatment planning systems (TPS) [14,26,27].…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of pencil beam algorithms in treatments involving low density inhomogeneities are well documented [2,5,6,7,15,20,29]. In this study, the AAA has been shown to account for the increase in lateral electron transport in terms of the broadening of the penumbra in low density material and predicting the reduction in central axis dose in such a low density heterogeneity.…”
Section: Discussionmentioning
confidence: 83%
“…Potentiell ist eine Genauigkeit von besser als ±2% zu erreichen [7]. Für den Anwender stellt sich im Rahmen der Dosisverordnung und Planbeurteilung die Frage nach den Auswirkungen bei Wechsel des Dosisalgorithmus [11]. In klinischen Beispielen sollen die Abweichungen in der Dosisverteilung von Plänen untersucht werden, die mit Pencil-Beam-und Monte-Carlo-Algorithmus berechnet wurden.…”
Section: Introductionunclassified